Anaerobic co-digestion of sewage sludge and food waste as a promising alternative for waste management and energy production - Hosen, Md Sabuj; Mansor, Mariatul Fadzillah; Mohammad, Zahangir Alam (IIUM Press, 2019)
Biogas is an economical and environmentally friendly renewable energy which can be produced by anaerobic digestion (AD). This biochemical method converts organic compounds (mainly from wastes) into a sustainable source of energy. Anaerobic co-digestion (AcoD) is a method combining more than one substrate to resolve the difficulties faced in a single substrate AD system. Solid wastes increases as the population increase so do the urbanization and industrial industries. Food waste and sewage sludge are examples of one of the solid wastes. Co-digesting of both substrates may improve process stabilization to increase biogas production and overcome the nutrients imbalance. Thus, anaerobic co-digestion has been recognized as a technology that could provide a clean renewable energy source and helps reduce the landfill problem. The objective of this paper is to investigate the recent achievements and perspectives on the interaction of co-digestion between food waste and sewage sludge to improve biogas production. This may provide valuable information on the optimization of combinations of substrates: food waste and sewage sludge and prediction of bioreactor performance.